Perilaku Nusyuz Suami terhadap Istri dan Implikasinya dalam Dinamika Pernikahan Masyarakat Kontemporer - Zharifah Mawaddah; Nova Fitria; Dwi Puspita Sari; Dwi Noviani (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to determine the nusyuz behavior of husbands to wives in the dynamics of contemporary community marriage. By using literature research and descriptive qualitative methods, the researcher seeks to understand the various aspects that contribute to the emergence of nusyuz behavior. Based on the results of the study, the researcher found several factors at play, including economic problems that burden the family, differences in socio-cultural values that may not be aligned, psychological issues that affect relationship dynamics, lack of deep religious understanding, and the influence of a less supportive family and social environment. Overcoming this problem requires strategic and collaborative measures involving various parties. The government and related institutions must take the initiative to create programs that educate the public about the importance of understanding and practicing Islamic teachings in accordance with the current context. Educational and religious institutions must be active in spreading the values of love, compassion and harmony taught by Islam. In addition, increasing public awareness about rights in marriage and the importance of gender equality is also key to preventing nusyuz.